Aplikasi Model SMAR pada Dua DAS Identik - I Indarto (Forum Geografi, 2012)
This paper shows the evaluation process (calibration and validation) of SMAR (The Soil Moisture Accounting Rainfall-Runoff) model at two identical catchment areas (Rawatamtu and Kloposawit) in East Java – Indonesia. Daily discharge, rainfall data and meteorological data were collected from measurement stations located at the catchments areas. Potential evapotranspiration (PET) was calculated from meteorological data extracted from existing stations located inside of the catchments. Calibration was conducted for periods of: 1991 to 1994, while validation was tested for periode of: 1995 to 2000. Model performance was evaluated by means of: (1) Nash-Sutcliffe coefficient, (2) correlation coefficient and (3) graphical comparation of calculated and measured flow. The result show the Nash-Sutcliffe coeffient = 0,73 and correlation coefficient = 0,86 for calibration period at Rawatamtu, while the same coefficients for Kloposawit are 0,54 and 0,74. Validation periode produce Nash-sutcliffe and correlation coefficients = 0,35 and 0,64 for Rawatamtu. While for Kloposawit the values are 0,48 and 0,81.